Input Type Effects On Students’ Written Narrative Responses - Mohd Izwan, Ramlee; Ernisa, Marzuki; Ahmed Shamsul Bahri, Mohamad Tuah (Centre for Language Studies, 2012)
This pilot study examines the differences of second language learners’ written responses when they are given two different input types with similar content. One input was through written narrative or visual only input, where the learners need to read, and the other was a performed narrative or audio-visual input, where learners need to watch. Learners were then required to respond to the input by completing the narratives. Results showed that there were no major discrepancies in terms of complete/incomplete storylines, length, and number of dialogues, but revealed that the audio-visual input influenced learners more as their responses have a stronger correspondence to the traits in the performance rather than the written narrative.